Mediating Entrepreneurial Creativity – The Effect of Human Resource Practices on Innovation (Malaysian Management Journal, 2019)
This research aims to evaluate the link between human resource practices (HRPs) and innovation with mediating effect of entrepreneurial creativity. This research uses the hierarchical analysis to examine data collected from entrepreneurs running 172 small and medium enterprises. The results show that (a) HRPs have a positive and significant effect on entrepreneurial creativity; (b) HRPs have statistically significant impact on innovation. These results provide empirical evidence that entrepreneurial creativity mediates the relationship between HRPs and innovation. Also, the findings provide evidence that the mediating role of entrepreneurial creativity causes improving employees' innovation. Also, the findings provide evidence that the mediating role of entrepreneurial creativity cause improving employees' innovation. By providing a cross-sectional examination of our model, we showed that HRPs and entrepreneurial creativity are of essence in shaping an innovative context. A comprehensive view on the triggers and outcomes of entrepreneurial creativity and innovation are needed, as the traditional unidirectional cause-effect rationale short in explaining how these concepts relate to one another and to entrepreneur experiences of HRPs.